Analysis for Science Librarians of the 2017 Nobel Prize in Physics: Making the Invisible Visible. Issue 1 (2nd January 2018) - Bohémier, Kayleigh Ayn
ABSTRACT: The 2017 Nobel Prize in Physics was awarded to Rainer Weiss, Kip S. Thorne, and Barry C. Barish. Each scientist played a critical role in the creation of the gravitational wave observatory that would eventually detect the first binary black hole merger on September 14, 2015. This paper provides a short overview of the history of gravitational wave searches, the LIGO team, and the discovery, followed by profiles of each scientist, with an emphasis on bibliometrics.